Cardiogenic pulmonary edema following β2 agonist infusion for acute bronchospasm - Benbernou, Soumia; Kambouche, Faouzia; Ghomari, Nabil (International Journal of Medicine, 2024)
We report the case of severe acute pulmonary oedema (APO) secondary to the administration of salbut-amol to a postpartum patient treated for acute bronchospasm. The diagnosis of acute pulmonary edema was suspected on the clinical examination, chest radiography, biological and echocardiographic findings. Rapid improvement under dobutamine and mechanical ventilation argue in favour of cardiogenic pulmo-nary edema.The young age of our patient, the absence of history of cardiovascular disease and the chro-nology of this complication onset regarded to salbutamol infusion could suggest β2 agonist involvement in this event. The improvement of cardiac function on echocardiography